Cross-cultural adaptation of the dysfunctional voiding score symptom (DVSS) questionnaire for Brazilian children - Adriano A. Calado; Eleazar M. Araujo; Ubirajara Barroso Jr.; Jose M. Bastos Netto; Miguel Zerati Filho; Antonio Macedo Jr.; Darius Bagli; Walid Farhat (International Brazilian Journal of Urology, 2010)
PURPOSE: To translate and culturally adapt the Dysfunctional Voiding Symptom Score (DVSS), questionnaire into Brazilian Portuguese. MATERIALS AND METHODS: The 10-item Dysfunctional Voiding Symptom Score (DVSS) was translated into Brazilian Portuguese according to a standard methodology: translation, synthesis, back-translation, Expert Committee, and pre-testing. After the translation process the final version was pre-tested and patient responses were analyzed to identify necessary modifications. Reliability was evaluated using the test-retest method, and internal consistency was assessed using Cronbach’s alpha. RESULTS: The Cronbach’s alpha coefficient was calculated in the test and retest phases. Internal consistency was found to be satisfactory, as confirmed by a Cronbach’s alpha coefficient of 0.76 for the test and 0.77 for the retest. A high degree of stability was found in the test/retest, with an intraclass correlation coefficient (ICC) of 0.960 (p < 0.001; 95% CI: 0.943-0.972). CONCLUSION: The cross-cultural adaptation process of the Dysfunctional Voiding Symptom Score questionnaire to be used on Brazilian children was successfully completed following internationally accepted methodologies.